Concepción, frontera paraguaya con el Mato Grosso, y la política económica de Carlos A. López. Entre la diplomacia y la guerra - Areces, Nidia R. (Centro de Historia Argentina y Americana, 2005)
The article intends to analyze the policy implemented by Carlos A. López, in particular in the border between Concepción and Mato Grosso in order to explain that the confiscation of all the State possessions, the consequent disposal of these resources to the international capital, and the laws of inviolability of private property and of disposition of lands, led to concentration in a few hands. This situation was consolidated after the War against Paraguay. The area, the demography, the production, and the system of land possession are addressed in order to reveal the operation of the Concepción Command between diplomacy and war as a strategic border with the Brazilian Empire (Imperio del Brasil).